Research Grant Proposal Writing Course for Students in Higher Institutions - Dable-Tupas, Genevieve; Toralba-Lupase, Victoria; Puyana, Juan C.; Găman, Mihnea-Alexandru (International Journal of Medical Students, 2022)
Research grant proposals have become part of the everyday life of every scientist working in the field of life sciences. Although most early career researchers begin working on research grant proposals during their doctorate, laying the foundation of this complicated task should occur during their undergraduate training. This editorial serves as an introduction into research grant proposal writing for students enrolled in higher education and tackles subjects such as choosing a research topic and writing a successful grant application, as well as possible challenges and funding opportunities that we considered appropriate for students and early career researchers.